(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The present paper employs conceptual tools of critical cognitive discourse research and rhetorical studies to explore patterns of legitimization discourse used by top Polish political parties to claim state leadership in the years 2015–2023. The first part studies the discourse of Law & Justice, a far-right conservative party ruling Poland from October 2015 to October 2023. It describes L&J’s strategies of leadership legitimization involving socio-ideological polarization, strategic generation of internal as well as external conflict, threat construction and crisis management. The second part analyzes the more moderate and cooperation oriented discourse strategies implemented by three opposition parties in the lead-up to the 2023 parliamentary elections, in which L&J finally lost power. The aim of the paper is to compare and contrast the two discourses, L&J’s and the opposition’s, to speculate about the longevity of radical populist discourses such as L&J’s. It is argued that a conflict-charged, polarized populist discourse can be an extremely powerful tool, able to grant long-term political leadership. At the same time, in a yet longer perspective, such a discourse runs a considerable risk of ‘wearing out’ and becoming vulnerable to more forward-looking and pragmatic leadership rhetoric, which presages political change.